2022
DOI: 10.21203/rs.3.rs-1756189/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut microbiota from patients with mild COVID-19 cause alterations in mice that resemble post-COVID syndrome

Abstract: Background There is mounting evidence that SARS-CoV-2 targets tissues beyond the respiratory tract. Long-term sequelae after COVID-19 are frequent and of major concern. Prolonged virus detection in the gut has been particularly intriguing. Of note, SARS-CoV-2 infection also disturbs the gut microbiota composition, a finding linked with disease severity in patients with COVID-19. Here, we aimed to characterize the functional role of the gut microbiota in the long-term consequences of COVID-19. To this end, we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 57 publications
1
10
0
1
Order By: Relevance
“…Severe dysbiosis and increased intestinal permeability might lead to the translocation of pathogens, toxins and cytokines to the circulatory system leading to severe complications and multi-organ failure [ 641 ]. The causal role of COVID-19-induced gastrointestinal dysbiosis in the development of symptoms and disease severity is further supported by results obtained with a gnotobiotic mouse model [ 642 ]. Fecal microbiota transplantation from COVID-19 patients to germ-free mice resulted in lung histopathology, an inflammatory cytokine profile, cognitive impairment, and increased susceptibility towards bacterial infection in the animal model indicating that pre-infection differences in microbiota composition might influence COVID-19 susceptibility and severity as well.…”
Section: Host Factorsmentioning
confidence: 73%
“…Severe dysbiosis and increased intestinal permeability might lead to the translocation of pathogens, toxins and cytokines to the circulatory system leading to severe complications and multi-organ failure [ 641 ]. The causal role of COVID-19-induced gastrointestinal dysbiosis in the development of symptoms and disease severity is further supported by results obtained with a gnotobiotic mouse model [ 642 ]. Fecal microbiota transplantation from COVID-19 patients to germ-free mice resulted in lung histopathology, an inflammatory cytokine profile, cognitive impairment, and increased susceptibility towards bacterial infection in the animal model indicating that pre-infection differences in microbiota composition might influence COVID-19 susceptibility and severity as well.…”
Section: Host Factorsmentioning
confidence: 73%
“…Higher levels of fungal translocation, from the gut and/or lung epithelium, have been found in the plasma of patients with long COVID compared with those without long COVID or SARS-CoV-2-negative controls, possibly inducing cytokine production 141 . Transferring gut bacteria from patients with long COVID to healthy mice resulted in lost cognitive functioning and impaired lung defences in the mice, who were partially treated with the commensal probiotic bacterium Bifidobacterium longum 25 .…”
Section: Gastrointestinal Systemmentioning
confidence: 99%
“…There are likely multiple, potentially overlapping, causes of long COVID. Several hypotheses for its pathogenesis have been suggested, including persisting reservoirs of SARS-CoV-2 in tissues 16,17 ; immune dysregulation [17][18][19][20] with or without reactivation of underlying pathogens, including herpesviruses such as Epstein-Barr virus (EBV) and human herpesvirus 6 (HHV-6) among others 17,18,21,22 ; impacts of SARS-CoV-2 on the microbiota, including the virome 17,[23][24][25] ; autoimmunity 17,[26][27][28] and priming of the immune system from molecular mimicry 17 ; microvascular blood clotting with endothelial dysfunction 17,[29][30][31] ; and dysfunctional signalling in the brainstem and/or vagus nerve 17,32 (Fig. 3).…”
Section: Introductionmentioning
confidence: 99%
“…We recently published in Gut to show that gut dysbiosis persisted for at least 6 months in patients with post-acute COVID-19 syndrome (PACS) 1. Murine and human studies have also reported microbial alterations associated with different PACS symptoms 2 3. With the pandemic entering its third year, PACS could potentially affect recovered individuals for over 1 year 4.…”
mentioning
confidence: 99%